Relationship of Academic Handicap, Cheating and Disruptive Behavior with Happiness among School Children - Awais Khalid, Arooj Zahra Rizvi, Rabab Zahra (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To examine the association between academic handicap, cheating and disruptive behavior with happiness among school children. Study Design: A cross-sectional correlational study. Place and Duration: This study was conducted at Private and Government School settings of Faisalabad City, Pakistan from January November 2020 to December 2020. Methodology: A total of 100 school students (50 in each group) were divided in to either: a) students who were not academically handicap, or b) who were academically handicap. Assessment of academic handicap was labeled by their respective class teachers as per “Academic Entitlement Questionnaire”. “Attitude towards Cheating Scale” was administered to evaluate the level of Cheating Behaviors and “Subjective Happiness Scale” was used to measure the “Level of Happiness”. Results: In a total of 100 students, 60 (60.0%) were boys and 40 (40.0%) girls. Majority of the participants, 77 (77%) were students of 9th class while 665 (65.0%) participant’s mothers were uneducated. Correlational analysis showed that academic handicap had a significant positive relationship with level of cheating and academic handicap had a significant negative relationship with level of happiness. Cheating and disruptive behavior had a significant negative relationship with level of happiness. The results indicated academic handicap and cheating and disruptive behavior are significant predictors of happiness. Practical Implications: Academic handicap students have more chance of cheating and disruptive behavior. Conclusion: Academic handicap reduces the level of happiness among school students. Students with cheating and disruptive behavior also report low level of happiness. Academic handicap students have more chance of cheating and disruptive behavior. Keywords: Academic handicap, cheating, disruptive behavior, happiness.